Acts Is Acts: Tautology and Theopolitical Form. Issue 4 (1st December 2020) - de Abreu, Maria José
Abstract: My aim in this article is threefold. First, to identify the function of tautology in Catholic Charismatic religious practices. Second, to analyze the formal structure of tautology as an embodied regime of citationality. Third, to expose how Charismatic practice both mirrors and anticipates the unfolding dramaturgy of sovereignty within current populism in Brazil and elsewhere. These aims converge in a reflection on the nature of political theater within and beyond political theology.